Radiotherapy for benign achillodynia. Long-term results of the Erlangen Dose Optimization Trial - Ott, Oliver J.; Jeremias, Carolin; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Fietkau, Rainer (Strahlentherapie und Onkologie, 2015)
The aim of this study was to evaluate the long-term efficacy of two dose-fractionation schedules for radiotherapy of achillodynia.Between February 2006 and February 2010, 112 evaluable patients were recruited for this prospective trial. All patients received orthovoltage radiotherapy. One course consisted of 6 fractions/3 weeks. In the case of insufficient remission of pain after 6 weeks, a second series was performed. Patients were randomly assigned to receive either single doses of 0.5 or 1.0 Gy. The endpoint was pain reduction. Pain was measured before, right after (early response), 6 weeks after (delayed response), and approximately 2 years after radiotherapy (long-term response) with a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).The median follow-up was 24 months (range, 11-56). The overall early, delayed, and long-term response rates for all patients were 84 %, 88 %, and 95 %, respectively. The mean VAS values before treatment for early, delayed, and long-term responses for the 0.5-Gy and 1.0-Gy groups were 55.7 ± 21.0 and 58.2 ± 23.5 (p = 0.53), 38.0 ± 23.2 and 30.4 ± 22.6 (p = 0.08), 35.5 ± 25.9 and 30.9 ± 25.4 (p = 0.52), and 11.2 ± 16.4 and 15.3 ± 18.9 (p = 0.16), respectively. The mean CPS values before treatment for early, delayed, and long-term responses were 8.2 ± 3.0 and 8.9 ± 3.3 (p = 0.24), 5.6 ± 3.1 and 5.4 ± 3.3 (p = 0.76), 4.4 ± 2.6 and 5.3 ± 3.8 (p = 0.58), and 2.2 ± 2.9 and 2.8 ± 3.3 (p = 0.51), respectively. No significant differences in long-term response quality between the two arms was found (p = 0.73).Radiotherapy is a very effective treatment for the management of benign achillodynia. For radiation protection, the dose for a radiotherapy series should not exceed 3.0 Gy.
EVALuna2:18279